2008
DOI: 10.1016/j.neurobiolaging.2007.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Stereologic estimates of total spinophilin-immunoreactive spine number in area 9 and the CA1 field: Relationship with the progression of Alzheimer's disease

Abstract: The loss of presynaptic markers is thought to represent a strong pathologic correlate of cognitive decline in Alzheimer's disease (AD). Spinophilin is a postsynaptic marker mainly located to the heads of dendritic spines. We assessed total numbers of spinophilin-immunoreactive puncta in the CA1 and CA3 fields of hippocampus and area 9 in 18 elderly individuals with various degrees of cognitive decline. The decrease in spinophilin-immunoreactivity was significantly related to both Braak neurofibrillary tangle (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 85 publications
(130 reference statements)
2
51
0
Order By: Relevance
“…Thus, dendritic spine loss in the PreC occurs incrementally across clinical diagnostic categories, a conclusion supported by our observation of a significant association between lower PreC dendritic spines and worsened performance on the neuropsychological tests relevant to PreC function (e.g., episodic memory, MMSE). These correlations in the PreC are similar to observations in the prefrontal cortex (PFC), where total numbers of spinophilin-ir dendritic spines correlated significantly with lower MMSE scores (Akram et al, 2008). However, in contrast to our study, Akram et al, reported a correlation of PFC spinophilin-ir spine measures with Braak staging for NFTs, but not with Aβ deposition.…”
Section: Discussionsupporting
confidence: 82%
“…Thus, dendritic spine loss in the PreC occurs incrementally across clinical diagnostic categories, a conclusion supported by our observation of a significant association between lower PreC dendritic spines and worsened performance on the neuropsychological tests relevant to PreC function (e.g., episodic memory, MMSE). These correlations in the PreC are similar to observations in the prefrontal cortex (PFC), where total numbers of spinophilin-ir dendritic spines correlated significantly with lower MMSE scores (Akram et al, 2008). However, in contrast to our study, Akram et al, reported a correlation of PFC spinophilin-ir spine measures with Braak staging for NFTs, but not with Aβ deposition.…”
Section: Discussionsupporting
confidence: 82%
“…It is also possible that AD causes a loss of GR-positive neurons which contributes to aberrant responses to increased corticosterone compared to WT controls. Indeed, the CA1 region, site of GR expression, is an area of considerable cell loss in AD (Mueller 2010; Akram 2008). …”
Section: Discussionmentioning
confidence: 99%
“…As the increase in SIPB-to-neuron ratio was only apparent between 10-month-old mice and 6-month-old mice rather than 6-month-old mice and 2-month-old mice, compensatory synaptic remodeling may only have been activated after substantial neurodegeneration. Similar observations have been observed for synaptophysin and other presynaptic proteins in neocortical association areas at Braak stage III of AD progression, prior to neurofibrillary pathology [42], for drebrin in the prefrontal cortex of patients with mild cognitive impairment followed by 40–60% decrease in severe AD [43], as well as for glutamatergic presynaptic bouton density in midfrontal gyrus of mild cognitive impairment patients [44], but not for total numbers of spinophilin-immunoreactive puncta in the CA1 and CA3 fields of hippocampus and area 9 in elderly individuals with various degrees of cognitive decline [45]. Moreover, Bronfman et al [46] described a “synaptic sprouting compensatory mechanism” in the hippocampus of aged PDAPP mice exhibiting atrophied cholinergic neurons in the medial septum.…”
Section: Discussionmentioning
confidence: 99%